Anti-inflammatory activity of kapok (ceiba pentandra) thorns in acute inflammation - Hashim, Ridzwan; Noordin, Nazirah; Zulkipli, Farah Hanis (Asian Academic Research Associates, 2014)
This research was conducted to evaluate the anti-inflammatory effect of Kapok (Ceiba pentandra) thorn extract. Standard screening tests were used to detect for the presence of secondary metabolites such as alkaloids, flavonoids, tannins, steroids, saponin and terpenoids. For anti-inflammatory effect, carrageenan induced rat paw edema model was used. Paw edema was initially induced on the right hind paw of rats by subplantar injection of 0.1ml of carrageenan solution. Then, the contralateral paw was injected with 0.1ml normal saline as control. Later, the extracts at doses 50 mg/kg and 500 mg/kg were injected intraperitoneally to the respective rats after 1 h post-carrageenan injection. Dexamethasone 5 mg/kg being used as a positive control the negative control received only saline solution. Paw volume measurements were recorded immediately by phlethysmometer before and at 1 h interval after the injection of carrageenan for a period of 7 h. The increase in paw volume was taken as the volume of edema for each rat. Anti-inflammatory activity was reported as percentage of edema inhibition compared to the control group. Based on the results obtained, the extracts showed anti-inflammatory activity at doses 50 mg/kg and 500 mg/kg. Higher reduction of paw volume was shown at the dose of 50 mg/kg compared to other treatments. In conclusion, the results showed the extract of C. pentandra thorn has anti-inflammatory property. This finding, therefore, lead to the basis of using the plant for the traditional treatment.